A Practical Model for Controlling a Group of Behaviour Problems in the Classroom - Rudner, Howard L. (Canadian Journal of Counselling and Psychotherapy, 2012)
A model combining a behavioural approach with Reality Therapy was used effectively in controlling a group of behaviour problems in the classroom. A behaviour modification design similar to the token economy system was established, together with a classroom atmosphere of warmth, understanding, and helping the children recognize what they were doing and their responsibility for it. In this design the children earned and/or lost certain rewards depending on their daily classroom behaviour. The model was used successfully in one elementary classroom, and it may be practical for other group situations as well. Some difficulties that may arise, and suggested solutions to these, are discussed.